DUAL COLLABORATOR “RE-START” CALL with the University of Canterbury, NZ on the “Linguistic Outcomes and Growth Onset of Speech (LOGOS)” project 120,000 Euro pending results. Petinou PI - (:unkn) unknown (My University, 2026)
RESEARCH EXPERIENCE